Unsatisfactory microbiological aspects of uht goat milk, soymilk and dairy beverage of goat milk and soy protein: A public health issue - Dos Anjos, Taís Ramalho [UNESP]; Cavicchioli, Valéria Quintana; Lima, Joyce Aparecida Santos [UNESP]; Vasconcellos, Alenia Naliato; Vaz, Andréia Cristina Nakashima; Rossi, Gabriel Augusto Marques [UNESP]; Campos-Galvão, Maria Emilene Martino; Todorov, Svetoslav Dimitrov; Mathias, Luis Antonio [UNESP]; Schocken-Iturrino, Rubén Pablo [UNESP]; Nero, Luís Augusto; Vidal, Ana Maria Centola (FapUNIFESP (SciELO), 2020)
Spore forming bacteria can play an important role in food quality and safety as spoilage and pathogenic microorganisms due to resistance to heat-treatment. However, there are limited number of studies focused on evaluate the microbiological quality and the occurrence of these bacteria in UHT goat milk, soymilk and dairy beverage of goat milk and soy protein. In this context, 75 samples of these beverages were evaluated regarding heterotrophic mesophilic microorganisms by conventional plate count and selective methods to detect microorganisms from Bacillus cereus group and Clostridium perfringens. Population counts greater than 104 CFU.ml-1 of heterotrophic mesophilic microorganisms were observed in 80% of the lots of goat milk and 100% of the lots of soymilk and dairy beverage of goat milk and soy protein. The presence of bacteria belonging to B. cereus group was observed in 16%, 52% and 44% of goat milk, soymilk and dairy beverage of goat milk and soy protein, respectively. C. perfringens was isolated from 8% samples of UHT soymilk. The frequency of genes hblA, hblB, hblC, nheA, nheB, nheC in 29 isolates obtained from these products was 62%, 48.2%, 96.5%, 79.3%, 68.9% and 79.3%, respectively. The microbiological quality of the evaluated products was unsatisfactory.
Keywords: Foodborne pathogens; Microbiology; PCR; Spores